(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study is to identify the correlation between social skills, desire to learn and anxiety in schools. Learning in the life of students with developmental disabilities enhanced cognitive and interpersonal abilities dramatically. The teaching in life skills has increased social and emotional skills of students with autism disability and can be used to develop social and emotional skills of children in schools of disability.